Dietary patterns and hypertension among daily laborers at Belawan Community Health Center - Eliza Juliana Hutabarat; Johannes Bastira Ginting; Pahala Maringan Jubel Simangunsong (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2026)
Background: Occupational health problems in the informal sector, particularly among daily laborers in coastal areas such as the working area of Belawan Community Health Center, require special attention. Heavy physical activity, environmental exposure, and individual characteristics are strongly suspected to be associated with fluctuations in blood pressure (systolic and diastolic) that may increase hypertension risk. This study aimed to determine the relationship between dietary patterns and hypertension among daily laborers in the working area of Belawan Community Health Center. Method: This quantitative study used a correlational analysis with a cross-sectional design. A sample of 92 daily laborers was selected using purposive sampling. Data were collected through interviews using a questionnaire and direct blood pressure measurement using a sphygmomanometer. Data were analyzed using the Chi-square test (α = 0.05) with SPSS. Results: Univariate analysis showed that most respondents had poor dietary patterns (64.1%) and were classified as having hypertension (44.6%) or prehypertension (28.3%). The Chi-square test yielded a p-value of less than 0.001, indicating a significant relationship between dietary pattern and hypertension among daily laborers in this population. Respondents with poor dietary patterns predominantly had elevated blood pressure, while those with good dietary patterns were more likely to have normal blood pressure. Conclusion: There is a significant relationship between dietary pattern and hypertension among daily laborers at Belawan Community Health Center. Regular health screening programs for informal sector workers in this area are recommended.